PENGARUH REVITALISASI POSYANDU TERHADAP STRATA POSYANDU DI PUSKESMAS MUTIARA KABUPATEN ASAHAN TAHUN 2020 - Sinaga, Eva Dona (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2025)
Posyandu is a form of health effort that is sourced from the community which is a tangible manifestation of community participation in health development. The importance of revitalization is an effort to revive the existing posyandu to rediscover the potential that is owned in improving the posyandu level. The purpose of this study was to analyze the effect of Posyandu Revitalization on the Posyandu Strata at MutiaraPuskesmasAsahan Regency in 2020.This study used a quantitative approach with observational research using a cross sectional design with a sample of 63 Posyandu cadres. The analysis used in this research was the univariate, then the bivariate test using the Chi Square test and the multivariate test using the multiple logistic regression test.The results of this study indicate that there was an effect of Posyandu cadre training which is carried out at least 2 x one year. . There is the influence of social support from the local government through the Lurah and providing incentives, transportation costs to posyandu cadres on the Posyandu Strata of MutiaraPuskesmas, Asahan Regency and social support is the most dominant variable having an influence on the Posyandu Strata with the Exp value. B was 9,429 and 95% CI: (1,137 - 78,162) indicates that good social support was 9,429 times the estimated probability of having a good posyandu strata at PuskesmasMutiaraAsahan Regency. It is suggested to increase and continue to provide incentives and transportation costs for posyandu cadres and there needs to be intensive motivation and support from the local government, health offices, puskesmas, and other related parties, so that in the future the performance of posyandu cadres can increase their participation and activity in providing service to the community.